A combined strain and compliance method for improving ASTM D6671 to measure the mixed modes I/II interlaminar fracture toughness. (1st August 2019) - Xu, W.; Guo, Z.Z.; Yu, Y.
Abstract: Mixed modes interlaminar delamination is one of the most common and serious failure modes in advanced carbon fiber reinforced composite materials. The ASTM standard D6671 is widely used to measure the mixed modes I/II interlaminar fracture toughness. One of the shortcomings of the current ASTM D6671 is the requirement of measuring the material Young's moduli from separate tensile tests and samples, which are time-consuming and source of uncertainty. Accurate and closed-form strain and compliance solutions to the mixed mode bending specimen are given in this paper. By using these solutions, a combined strain and compliance method is proposed to measure the mixed modes I/II interlaminar fracture toughness, which avoids the measurement of the Young's moduli from separate tests and specimens. The average difference between the mixed modes fracture toughness measured from the present method and that from ASTM D6671 is within 5%, thus the present paper provides a consistent and simple method for measuring the mixed modes I/II interlaminar fracture toughness.